Influence of Environment and Planting Patterns on Insect Diversity in Cabbage Fields - Nasik, Isman; Tarwodjo, Udi; Rahadian, Rully (Jurnal Biologi Tropis, 2024)
Insect diversity in agricultural ecosystems is influenced by cropping patterns and physical environmental conditions. In cabbage cultivation, it is crucial to understand cropping management to support the sustainability of agricultural ecosystems. This study aims to examine the effects of cropping patterns and environmental factors on insect diversity and evaluate the effectiveness of sticky traps in cabbage fields. Monoculture and polyculture systems (a combination of cabbage and lettuce) were tested to assess differences in insect community structure based on diversity, abundance, evenness, similarity, and dominance. The study was conducted from July to August 2019 using sticky traps in yellow, green, and white colors. The analysis included the Shannon-Wiener diversity index (H'), evenness (e), dominance (D), species richness, and Sorensen and t-Hutcheson tests. Environmental factors such as temperature and humidity were also analyzed to assess their impact on insect community structure. The results showed no significant differences in insect community structure between monoculture and polyculture systems, with the Aleyrodidae family dominating both systems. Temperature and humidity significantly influenced the insect community. Yellow sticky traps were found to be the most effective in capturing insects compared to green and white traps.